Lysine crotonylation in disease: mechanisms, biological functions and therapeutic targets - Yu Ji; Shanshan Liu; Yiqiao Zhang; Yiyang Min; Luyang Wei; Chengjian Guan; Huajing Yu; Zhongtao Zhang (Epigenetics & Chromatin)
Abstract Lysine crotonylation (Kcr), a previously unknown post-translational modification (PTM), plays crucial roles in regulating cellular processes, including gene expression, chromatin remodeling, and cellular metabolism. Kcr is associated with various diseases, including neurodegenerative disorders, cancer, cardiovascular conditions, and metabolic syndromes. Despite advances in identifying crotonylation sites and their regulatory enzymes, the molecular mechanisms by which Kcr influences disease progression remain poorly understood. Understanding the interplay between Kcr and other acylation modifications may reveal opportunities for developing targeted therapies. This review synthesizes current research on Kcr, focusing on its regulatory mechanisms and disease associations, and highlights insights into future exploration in epigenetics and therapeutic interventions.